UMP offers Mandarin course for industry workers - UMP, PNC (2018)
Universiti Malaysia Pahang (UMP) signed a Memorandum of Agreement (MoA) with Steel Alliance (M) Sdn. Bhd. (ASSB) and ATOZ Solution Sdn. Bhd. in a move to brush up Mandarin among the industry workers.